The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1097/01.gme.0000094394.59028.46
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of soy isoflavones on bone mineral content was modified by years since menopause, body weight, and calcium intake: a double-blind, randomized, controlled trial

Abstract: The independent effect of soy on the maintenance of hip BMC is more marked in women in later menopause or those with lower BW or calcium intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 32 publications
2
27
0
2
Order By: Relevance
“…Our literature search identified 31 RCTs. Twenty-two studies were excluded because of lack of indices of interest (Agnusdei et al, 1997a, b;Gambacciani et al, 1997a, b;Potter et al, 1998;Alekel et al, 2000;Wangen et al, 2000;Clifton-Bligh et al, 2001;Katase et al, 2001;Anderson et al, 2002;Chiechi et al, 2002;Lucas et al, 2002;Chen et al, 2003Chen et al, , 2004Jones et al, 2003;Schult et al, 2003;Atkinson et al, 2004;Harkness et al, 2004;Olsen et al, 2004;Mori et al, 2004a, b), non-randomization (Dalais et al, 1998), lack of a control group (Agnusdei et al, 1997a, b), insufficient original data or baseline values (Gambacciani et al, 1997a, b;Khalil et al, 2002). Thus, nine studies with a total of 432 subjects were included in this meta-analysis, in which five studies had quality score of five; three studies had quality score of four and one study had quality score of three (Morabito et al, 2002;Uesugi et al, 2002;Yamori et al, 2002;Arjmandi et al, 2003Arjmandi et al, , 2005Dalais et al, 2003;Brooks et al, 2004;Mori et al, 2004a, b;Nikander et al, 2004) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Our literature search identified 31 RCTs. Twenty-two studies were excluded because of lack of indices of interest (Agnusdei et al, 1997a, b;Gambacciani et al, 1997a, b;Potter et al, 1998;Alekel et al, 2000;Wangen et al, 2000;Clifton-Bligh et al, 2001;Katase et al, 2001;Anderson et al, 2002;Chiechi et al, 2002;Lucas et al, 2002;Chen et al, 2003Chen et al, , 2004Jones et al, 2003;Schult et al, 2003;Atkinson et al, 2004;Harkness et al, 2004;Olsen et al, 2004;Mori et al, 2004a, b), non-randomization (Dalais et al, 1998), lack of a control group (Agnusdei et al, 1997a, b), insufficient original data or baseline values (Gambacciani et al, 1997a, b;Khalil et al, 2002). Thus, nine studies with a total of 432 subjects were included in this meta-analysis, in which five studies had quality score of five; three studies had quality score of four and one study had quality score of three (Morabito et al, 2002;Uesugi et al, 2002;Yamori et al, 2002;Arjmandi et al, 2003Arjmandi et al, , 2005Dalais et al, 2003;Brooks et al, 2004;Mori et al, 2004a, b;Nikander et al, 2004) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…18 Table 2 lists studies on humans in response to the effect of SI. Some studies showed significant prevention in bone loss (BMD/BMC) over the duration of the studies 35,46,47,[58][59][60][61][62][63][64][65][66][67][68] ; others did not prove to have significant effects. 18,[69][70][71][72][73][74][75][76][77][78][79] Bone remodeling is a slow process.…”
Section: Intervention Materialsmentioning
confidence: 99%
“…Previous animal studies have shown that genistein treatment increased bone mineral density (BMD) and improved bone biomechanical performance in ovariectomized (OVX) rodents [12,13] . Clinical studies have also demonstrated that phytoestrogen can effectively increase the BMD of vertebrae and hip bones in postmenopausal women without side effects, which suggested that genistein plays an important role in the regulation of bone formation and bone resorption [14][15][16][17] . phosDose-dependent effects of genistein on bone homeostasis in rats' mandibular subchondral bone www.chinaphar.com Li YQ et al Acta Pharmacologica Sinica npg phatase (ALP) and osteocalcin (OC) are widely used markers for bone formation.…”
Section: Introductionmentioning
confidence: 99%